An Analysis of Information Technology-Based Educational Human Resource Development Strategies at the Higher Education Level - Jumaidi Nur; Marrieta Moddies Swara; Tugiman; Ida Farida; Sri Utami (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This qualitative study aimed to analyze information technology-based educational human resource development strategies at the higher education level at Kutai Kartanegara University. The study utilized an exploratory and descriptive research design, employing interviews and document analysis as data collection methods. The participants included vital administrators, faculty members, and students from various departments within the university. The findings revealed that information technology was crucial in shaping educational human resource development strategies at Kutai Kartanegara University. The university has implemented various IT-based initiatives to enhance teaching and learning experiences, improve administrative processes, and foster professional development among faculty members. Regarding teaching and learning, the university has integrated various IT tools and platforms into the curriculum, such as learning management systems, multimedia resources, and virtual classrooms. These initiatives provided students with flexible learning opportunities, interactive course materials, and collaborative spaces for knowledge exchange. Moreover, the university has implemented IT-based professional development programs for faculty members, including training workshops, online resources, and communities of practice. The findings provide valuable insights for educational institutions seeking to leverage IT to enhance their human resource development strategies at the higher education level. Keywords: Educational Human Resource Development, Educational Human Resource Strategy, Technology-Based Education